Determinants of 1‐year changes in disease‐specific health status in patients with advanced chronic obstructive pulmonary disease: A 1‐year observational study. Issue 3 (26th March 2014) - Wilke, Sarah; Spruit, Martijn A; Wouters, Emiel FM; Schols, Jos MGA; Franssen, Frits ME; Janssen, Daisy JA
<x xml:space="preserve">Abstract</x> We aimed to identify baseline and longitudinal determinants of change in disease‐specific health status in patients with advanced chronic obstructive pulmonary disease (COPD). Demographic and clinical characteristics as well as disease‐specific health status (St George's Respiratory Questionnaire, SGRQ) were assessed in 105 outpatients with advanced COPD at baseline and at 4, 8 and 12 months. Eighty‐five patients (81.0%) had complete SGRQ data at baseline and 12 months and were included in analyses. Stepwise multiple regression analysis revealed that lower SGRQ total score, higher depression scores and longer time needed to complete the Timed Up and Go (TUG) test at baseline, as well as increase in time needed to complete the TUG test and increase in dyspnoea during the 1‐year follow‐up period, were predictors of deterioration in disease‐specific health status. The current study reinforces the stimulation of physical mobility and the targeting of dyspnoea as components for treatment programs to optimize disease‐specific health status in patients with advanced COPD.